2020
DOI: 10.1093/zoolinnean/zlaa074
|View full text |Cite
|
Sign up to set email alerts
|

Near-complete phylogeny of extant Crocodylia (Reptilia) using mitogenome-based data

Abstract: Abstract Species of the order Crocodylia are mostly large, predatory and semi-aquatic reptiles. Crocodylia, the closest living relatives of birds, first appeared in the Late Cretaceous period. In the present study, the complete mitochondrial (mt) genomes of 19 Crocodylia species, including two species (Melanosuchus niger and Caiman yacare) that have not been previously sequenced for mitogenomes, were processed through Illumina sequencing to offer genetic resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 71 publications
11
39
0
Order By: Relevance
“…The vast majority of published phylogenetic analyses based exclusively on morphological data have recovered Gavialidae in a basal position within Crocodylia, while Alligatoroidea and Crocodyloidea (including Tomistominae) are usually found forming a separate clade (=Brevirostres; Norell, 1989;Brochu, 1999Brochu, , 2003Salisbury et al, 2006;Salas-Gismondi et al, 2016;Jouve, 2016). In contrast, results from molecular data are in opposition to those derived from morphological datasets alone by suggesting that Gavialis Oppel, 1811 and Tomistoma Müller, 1846 are actually closely related (Densmore, 1983;Densmore & Owen, 1989;Hass et al, 1992;Gatesy et al, 2003;McAliley et al, 2006;Willis et al, 2007;Oaks, 2011;Pan et al, 2020). In recent years, several studies that performed analyses combining morphological and molecular data have managed to recover topologies that are in Q u i n k a n a t i m a r a Figure 34 Reduced 50% majority-rule consensus topology from the first phylogenetic analysis, run without using the Implied Weighting method.…”
Section: Phylogenymentioning
confidence: 87%
“…The vast majority of published phylogenetic analyses based exclusively on morphological data have recovered Gavialidae in a basal position within Crocodylia, while Alligatoroidea and Crocodyloidea (including Tomistominae) are usually found forming a separate clade (=Brevirostres; Norell, 1989;Brochu, 1999Brochu, , 2003Salisbury et al, 2006;Salas-Gismondi et al, 2016;Jouve, 2016). In contrast, results from molecular data are in opposition to those derived from morphological datasets alone by suggesting that Gavialis Oppel, 1811 and Tomistoma Müller, 1846 are actually closely related (Densmore, 1983;Densmore & Owen, 1989;Hass et al, 1992;Gatesy et al, 2003;McAliley et al, 2006;Willis et al, 2007;Oaks, 2011;Pan et al, 2020). In recent years, several studies that performed analyses combining morphological and molecular data have managed to recover topologies that are in Q u i n k a n a t i m a r a Figure 34 Reduced 50% majority-rule consensus topology from the first phylogenetic analysis, run without using the Implied Weighting method.…”
Section: Phylogenymentioning
confidence: 87%
“…Other studies obtained divergence times for Crocodylia using only molecular data, including Oaks (2011) and the recently published work of Pan et al . (2020). These two studies found the most recent common ancestor of all living caimanines to be much younger (Eocene and Oligocene–Miocene, respectively) than our estimates for Caimaninae, even for crown caimanines (70.95–62.55 Ma; median = 66.34 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…in the case of Pan et al . 2020) or the omission of some recently discovered taxa in node‐dating analyses (i.e. in the case of Oaks 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although using fossilized birth–death tip dating in this way is common practice for time-calibrating trees containing extinct taxa and has previously been used to date Crocodylomorpha phylogenies [ 4 ], we recovered divergence dates among extant taxa that are much more recent than estimates based on molecular evidence [ 51 ]. To be able to evaluate the effects of different dating approaches, we created a fourth phylogenetic hypothesis by modifying topology (C) to have divergence dates among extant taxa matching the mean node dates from a recent mitogenome-based phylogeny [ 51 ].…”
Section: Methodsmentioning
confidence: 99%